(untitled) (Bangladesh Journal of Animal Science, 2014)
This study was conducted in Boyra and Sutiakhali villages under Sadar upazila of Mymensingh district to know the present status of backyard poultry production system. The survey data were collected from 40 randomly selected farmers having 20 from each village by interviewing them. The data were then analyzed statistically. All the selected farmers reared deshi chicken and about 54% of them reared deshi duck only. It was also found that highest proportion (75%) of farmers reared both chicken and duck together, followed by 17.5% reared only chicken and 7.5% reared chicken, duck and pigeon at a time. The average population per household of chicken, duck and pigeon were 10.4, 9.95 and 4.0, respectively, in both villages. All farmers reared poultry in semi-scavenging system. About 55% farmers kept poultry in their dwelling house. Farmers were used boiled rice, rice polish, paddy and broken rice to fed the birds. About 62% farmers were used rice and rice polish to make diet for chicken and ducks. Farmers provided around 49g and 108g supplemental diet to each chicken and duck per day, respectively and about 65% farmers provided this diet twice a day. Majority of farmers did not use feeder and waterer (about 75% and 87.5% respectively). Age at sexual maturity of Chicken and duck were around 189 days and 195 days, respectively. Adult weight of chicken and duck were 1192.5g and 1690g, respectively. The weights of chicken and duck eggs were 39.02 and 62.5g, respectively. The hatchability of chicken and duck eggs ranged between 69-80% and 76-90% with an average of 75.97 and 83%, respectively. Majority of the farmers mentioned that the most prevalent diseases of chicken and duck were New castle and cholera (about 51% and 49%, respectively). A large number of farmers (86%) did not vaccinate their poultry. Mortality of chicken and duck were calculated about 28% and 20%, respectively. Farmers collected chicks and ducklings from market and neighbor but most of the farmers (50% for chicks and 43% for ducks) incubate eggs under the broody hen. It was concluded that backyard poultry farmers are low producers and chicken and duck were found to be the most common poultry species reared by the farmers. DOI: http://dx.doi.org/10.3329/bjas.v43i1.19382 Bang. J. Anim. Sci. 2014. 43 (1): 30-37